Bash for data scientists - Campesato, Oswald (Mercury Learning & Information, 2023)
This book introduces an assortment of powerful command line utilities that can be combined to create simple, yet powerful shell scripts for processing datasets. The code samples and scripts use the bash shell, and typically involve small datasets so you can focus on understanding the features of grep, sed, and awk. Companion files with code are available for downloading from the publisher. FEATURES:Provides the reader with powerful command line utilities that can be combined to create simple yet powerful shell scripts for processing datasetsContains a variety of code fragments and shell scripts for data scientists, data analysts, and those who want shell-based solutions to "clean" various types of datasetsCompanion files with code.